2015
DOI: 10.3109/09513590.2015.1116509
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal malignancy in 202 female patients with disorders of sex development containing Y-chromosome material

Abstract: The objective of this study was to examine risks for gonadal malignancy in a large sample of adult female patients with disorders of sex development (DSD). A retrospective-observational study was conducted from July 1992 to March 2015 and 202 women with DSD were enrolled. Tumor risks for different types of DSD were measured. We found that the patients' total gonadal-malignancy risk was 18.3% (37/202). Tumors included gonadoblastoma (n = 11), seminoma (n = 8), dysgerminoma (n = 5), choriocarcinoma (n = 1), sert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 25 publications
0
50
2
Order By: Relevance
“…Phenotypic female DSD patients with Y chromosome or Y‐derived sequence have a significantly increased risk of GCTs compared to the general population, and prophylactic bilateral gonadectomy is currently recommended to prevent tumour occurrence . The previous study of our centre analysed proportion and malignancy rate of different clinical categories of DSD in a subgroup of this cohort. We now further included 121 patients and extended the observations on a larger group of patients to analyse detailed aspects of tumour risk, including the malignancy risk under the age of 20 and over the age of 20 in each category, other features of patients with tumours (the gonad position, sex hormone levels and utility of tumour markers) and our experience of HRT after surgery in DSD individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic female DSD patients with Y chromosome or Y‐derived sequence have a significantly increased risk of GCTs compared to the general population, and prophylactic bilateral gonadectomy is currently recommended to prevent tumour occurrence . The previous study of our centre analysed proportion and malignancy rate of different clinical categories of DSD in a subgroup of this cohort. We now further included 121 patients and extended the observations on a larger group of patients to analyse detailed aspects of tumour risk, including the malignancy risk under the age of 20 and over the age of 20 in each category, other features of patients with tumours (the gonad position, sex hormone levels and utility of tumour markers) and our experience of HRT after surgery in DSD individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The study retrospectively investigated the medical records of 292 patients, who were diagnosed DSD with Y chromosome or Y‐derived sequence and received bilateral gonadectomy at Peking Union Medical College Hospital from January 1996 to March 2016. Our centre has previously presented a subgroup of this cohort comprising 171 individuals . We now further included 121 patients of DSD and extended the observations on a larger group of patients to analyse detailed aspects of tumour risk.…”
Section: Methodsmentioning
confidence: 99%
“…This condition affects one in 4,500–5,000 live births, and encompasses a wide spectrum of phenotypic presentations including normally virilized males or undervirilized males, patients with ambiguous genitalia, and normal phenotypic females . The diagnosis of GD places the patient at an increased risk (15–60%) for developing gonadal germ cell tumors (GCT), especially gonadoblastoma . The presence of Y‐chromosome material or an intraabdominal gonad position increases the risk of developing a gonadal GCT …”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact, metastatic spread in the early stages is not common . 5 It has been suggested that highly cellular tumors with a small amount of stroma and lymphocytic infiltration as well as marked atypia and high mitotic activity tend to be more aggressive (12). However, there is still no good evidence for predicting the behavior of neoplasm by its histologic appearance (8,17).…”
Section: Discussionmentioning
confidence: 99%
“…Embryonal carcinoma, yolk sac tumor, clear cell carcinoma, malignant lymphoma, sex cord stromal tumors including sertoli leydig and steroid cell tumor are the main differential diagnoses of dysgerminoma on histologic examination (5,10,14). Distinct cytologic features, lobulated architecture with lymphocytes in the interlobular fibrous septa, and immunohistochemistry are helpful for an accurate diagnosis (5).…”
Section: Discussionmentioning
confidence: 99%